PENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA KABUPATEN SANGGAU BERDASARKAN PERATURAN DAERAH KABUPATEN SANGGAU NOMOR 15 TAHUN 2017 TENTANG KETERTIBAN UMUM - NIM. A1011201154, MARIO CHRISTIAN LISERO (Jurnal Fatwa Hukum, 2025)
AbstractEMPLOYMENT OF STREET VENDORS BY THE SANGGAU DISTRICT PAMONG PRAJA POLICE UNIT BASED ON THE REGULATORY REGULATION OF SANGGAU DISTRICT NUMBER 15 YEAR 2017 ON PUBLIC LIBERTY. The thesis is entitled Controlling Street Vendors by the Sanggau Regency Pamong Praja Police Unit Based on Regional Regulation Sanggau Regency Number 15 of 2017 concerning Public Order. The formulation of the problem of this research This thesis is "What Efforts Should Be Made Pamong Praja Police Unit of Sanggau Regency Based on Regional Regulation Sanggau Regency Number 15 of 2017 concerning Public Order to Street Vendors Who Violate the Law in Sanggau Regency. Street Vendors Who Violate the Law in Sanggau Regency, Kapuas District to Increased Order?". Then the objectives of this study are: (a) To know what factors cause the ineffective implementation and enforcement of the Local Regulation on Public Order by the Pamong Police Public Order by the Pamong Praja Police of Sanggau Regency; and (b) To determine what efforts should be made by the Pamong Praja Police of Sanggau Regency in the implementation and enforcement of Public Order. Furthermore, the research method used is empirical legal research with descriptive research properties. The results obtained from this study indicate that the Regional Government of Sanggau Regency is still lacking in curbing and enforcing public order for violating street vendors, especially in the Kapuas District area, both due to regional regulations and regent regulations that are less detailed in providing agency authority and lack of coordination between related OPDs. Then Satpol PP must be more active in curbing street vendors who violate public order in order to enforce Regional Regulations and maintain the dignity of the agency. Satpol PP can also provide and play an active role in the formulation of Regional Regulations on public order and street vendors as well as in empowering these street vendors.  Keywords : Employments; Pamong Praja Police Unit; Street Vendors.      AbstrakPENERTIBAN PEDAGANG KAKI LIMA OLEH SATUAN POLISI PAMONG PRAJA KABUPATEN SANGGAU BERDASARKAN PERATURAN DAERAH KABUPATEN SANGGAU NOMOR 15 TAHUN 2017 TENTANG KETERTIBAN UMUM. Skripsi ini berjudul Penertiban Pedagang Kaki Lima Oleh Satuan Polisi Pamong Praja Kabupaten Sanggau Berdasarkan Peraturan Daerah Kabupaten Sanggau Nomor 15 Tahun 2017 Tentang Ketertiban Umum. Adapun yang menjadi rumusan masalah dari penelitian skripsi ini adalah "Upaya Apa Yang Harus Dilakukan Satuan Polisi Pamong Praja Kabupaten Sanggau Berdasarkan Peraturan Daerah Kabupaten Sanggau Nomor 15 Tahun 2017 Tentang Ketertiban Umum Kepada Pedagang Kaki Lima Yang Melanggar Hukum Di Kabupaten Sanggau, Kecamatan Kapuas Untuk Peningkatan Ketertiban?". Kemudian tujuan dari penelitian ini adalah: (a) Mengetahui faktor apa yang menyebabkan belum efektifnya penerapan dan penegakan Perda Ketertiban Umum oleh Polisi Pamong Praja Kabupaten Sanggau; dan (b) Mengetahui upaya apa yang harus dilakukan oleh Polisi Pamong Praja Kabupaten Sanggau dalam penerapan dan penegakan Ketertiban Umum. Selanjutnya metode penelitian yang digunakan adalah penelitian hukum empiris dengan sifat penelitian deskriptif. Hasil yang didapat dari penelitian ini menunjukkan bahwa Pemerintah Daerah Kabupaten Sanggau masih kurang dalam menertibkan dan menegakkan ketertiban umum bagi para PKL yang melanggar khususnya di wilayah Kecamatan Kapuas baik itu karena peraturan daerah dan peraturan bupati yang kurang rinci dalam memberikan wewenang instansi maupun kurangnya koordinasi antar OPD terkait. Kemudian Satpol PP harus lebih aktif lagi dalam menertibkan PKL yang melanggar ketertiban umum dalam rangka menegakkan Peraturan Daerah dan menjaga marwah instansi. Satpol PP juga dapat memberikan dan berperan aktif dalam perumusan Peraturan Daerah tentang ketertiban umum dan PKL maupun dalam memberdayakn PKL ini.  Kata Kunci : Penertiban; Pedagang Kaki Lima; Satuan Polisi Pamong Praja.